Metabolically healthy obesity: the low-hanging fruit in obesity treatment? - Stefan, Norbert; Häring, Hans-Ulrich; Schulze, Matthias B (The lancet. Diabetes & endocrinology, 2018)
Obesity increases the risk of several other chronic diseases and, because of its epidemic proportions, has become a major public health problem worldwide. Alarmingly, a lower proportion of adults have tried to lose weight during the past decade than during the mid-1980s to 1990s. The first-line treatment option for obesity is lifestyle intervention. Although this approach can decrease fat mass in the short term, these beneficial effects typically do not persist. If a large amount of weight loss is not an easily achievable goal, other goals that might motivate people with obesity to adopt a healthy lifestyle should be considered. In this setting, the concept of metabolically healthy obesity is useful. Accumulating evidence suggests that, although the risk of all-cause mortality and cardiovascular events might be higher in people with metabolically healthy obesity compared with metabolically healthy people of a normal weight, the risk is substantially lower than in individuals with metabolically unhealthy obesity. Therefore, every person with obesity should be motivated to achieve a normal weight in the long term, but more moderate weight loss sufficient for the transition from metabolically unhealthy obesity to metabolically healthy obesity might also lower the risk of adverse outcomes. However, how much weight needs to be lost for this transition to occur is under debate. This transition might be supported by lifestyle factors-such as the Mediterranean diet-that affect cardiovascular risk, independent of body fat. In this Series paper, we summarise available information about the concept of metabolically healthy obesity, highlight gaps in research, and discuss how this concept can be implemented in clinical care.